Adaptive institutions in social-ecological systems governance: A synthesis framework. Issue 53 (November 2015) - Koontz, Tomas M.; Gupta, Divya; Mudliar, Pranietha; Ranjan, Pranay
Highlights: This paper offers a theoretical framework to guide research on adaptive institutions. Studies across two decades were synthesized to identify important precursors of adaptive institutions. This paper highlights the importance of federalism, polycentricity, networks, and learning and suggests avenues for further inquiry. Abstract: Adaptive governance of social-ecological systems depends on adaptive institutions. Efforts to understand the factors affecting adaptive institutions have identified many variables, but our understanding is constrained by multiple definitions of these concepts. In this article, we synthesize across two decades of studies relating to adaptive institutions. After clarifying some definitional confusion in the literature, we provide a theoretical framework to guide research on purposeful institutional change. While numerous scholars have identified a wide variety of important factors, we find that many of these factors can be traced back to (1) federalism and polycentricity and (2) networks and learning. Our synthesis suggests several avenues for future research centered on these factors. For example, how might the potential negative effects of key facilitating variables such as polycentricity (e.g., racial segregation and income sorting) and heterogeneous networks (e.g., increased coordination costs) hinder adaptive institutions? How can learning through both scientific and time-and-place knowledge promote adaptive institutions? More broadly, social science can play an important role in identifying factors that foster adaptability in different contexts, so that policy makers can promote such adaptability.